Stimulation of human lymphocytes by a vaccine strain of Francisella tularensis. - Tärnvik, A (1975)
An immune response to Francisella tularensis was demonstrated in man by the lymphocyte stimulation test. Peripheral blood lymphocytes were obtained from 26 individuals vaccinated with a viable tularemia vaccine, from 29 unvaccinated individuals, and from two patients who had recently undergone tularemia. The lymphocytes were incubated in the presence of various dilutions of heat-killed bacteria of the vaccine strain. The bacteria induced a deoxyribonucleic acid synthesis in the lymphocytes from 18 of the vaccinated individuals and from the two patients which was higher than that in the lymphocytes from any of the unvaccinated individuals. The deoxyribonucleic acid synthesis was maximal after about 6 days of incubation irrespective of concentration of bacteria. Lymphocytes from vaccinated and unvaccinated individuals were stimulated by two unrelated agents, tuberculin purified protein derivative and pokeweed mitogen. Lymphocytes from the vaccinated individuals did not show a higher response to these agents than did those of the unvaccinated. This suggests that the lymphocyte response to the Francisella bacteria was not due to a nonspecific activation. The vaccine-induced lymphocyte stimulation did not correlate with serum antibodies agglutinating F. tularensis antigen.